2022
DOI: 10.1002/bse.3071
|View full text |Cite
|
Sign up to set email alerts
|

A stakeholder perspective on managing tensions in hybrid organizations: Analyzing fair trade for a sustainable development

Abstract: This paper presents a stakeholder perspective to study tensions in hybrid organizations (HOs). In this study, we investigate social enterprises (SEs) as emblematic cases of HO. The paper responds to literature that calls for studies about the interactions with stakeholders and proposes the relational paths SEs can implement to alleviate the emerging tensions between environmental–social and business goals. It also contributes to the academic debate offering empirical evidence on HO‐related tensions. Solving th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…For instance, a survey of Australian SVs found that customer orientation is positively associated with performance in environmental, social, and economic domains (Pinheiro et al, 2021;Yu et al, 2022). Another survey of British SVs found that customer orientation improves the financial and social performance of SVs (Gigliotti and Runfola, 2022). Other studies related to SV performance reported the positive effect of entrepreneurial orientation-a form of organizational capability-on the SVs' financial but not social performance (Lee and Chandra, 2020;Yu et al, 2022) and the positive influence of business planning on the performance (financial and social) among SVs (Cheah et al, 2019).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, a survey of Australian SVs found that customer orientation is positively associated with performance in environmental, social, and economic domains (Pinheiro et al, 2021;Yu et al, 2022). Another survey of British SVs found that customer orientation improves the financial and social performance of SVs (Gigliotti and Runfola, 2022). Other studies related to SV performance reported the positive effect of entrepreneurial orientation-a form of organizational capability-on the SVs' financial but not social performance (Lee and Chandra, 2020;Yu et al, 2022) and the positive influence of business planning on the performance (financial and social) among SVs (Cheah et al, 2019).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The SV literature documented a positive association between marketing efforts and performance (social and financial) of SVs (e.g. Beisland et al, 2021;Gigliotti and Runfola, 2022). However, these studies have yet to examine the influence of another key mechanism that influence performance which is market turbulence.…”
Section: Marketing Capabilities and Social Performance Under Market T...mentioning
confidence: 99%
See 2 more Smart Citations
“…There is a difficulty in categorizing and understanding everything that is not related to the industry itself or to government or governmental institutions (Avelino & Wittmayer, 2016). Different actors play roles in this transition scenario, and there are imbalances of power (De Sousa Jabbour et al, 2020; Frantzeskaki & Rok, 2018; Gigliotti & Runfola, 2022).…”
Section: Introductionmentioning
confidence: 99%